A Systematic Review of Drug-Induced Pemphigoid - Matthew J. Verheyden; Asli Bilgic; Dédée F. Murrell (Medical Journals Sweden, 2020)
Bullous pemphigoid is an autoimmune subepithelial disease characterised by pruritus followed by urticarial plaques and finally bullae on the skin and mucosa. Drug-associated bullous pemphigoid (DABP) is a term used to describe instances of bullous pemphigoid demonstrating clinical, histological, or immunopathological features identical or similar to those of the idiopathic form of bullous pemphigoid, associated with the systemic ingestion, or topical application of particular drugs. In this study, we conducted a comprehensive search of the literature according to PRISMA guidelines and a total of 170 publications were included in the final qualitative analysis. In conclusion, 89 drugs were implicated in DABP. The strongest evidence for DABP is seen with gliptins, PD-1/PD-L1 inhibitors, loop diuretics, penicillin and derivatives. An appreciation of the medications associated with bullous pemphigoid enables clinicians to identify potential cases of DABP earlier and cease the offending medication.